Overview Of Challenges in Drafting ICT Contract - Ayub, Zainal Amin (2022)
The world has moved to the new industrial era known as the Industrial Revolution of 4.0 (IR4.0). Alongside, there is an exponential growth of information technology in support of the coming of I R4.0, where the use of information technology products either software or hardware products, have increased rapidly. This development also reflects an increase in software development or the buying of hardware. Consequently, contracts need to be signed for the purchase of the hardware or the development software between the developer, vendor, purchaser or owner. Applying a pure doctrinal research methodology, this article aims to examine the challenges in drafting the information communication technology (ICT) contract. This article lays down the dos and don'ts or challenges in drafting the ICT contract which normally involves Service Level Agreement (SLA). The SLA is one of the main components in an ICT contract that need to be given special scrutiny by the parties. There are phases of drafting an ICT contract that needs the involvement of the technical team, and not just the legal team, in every phase of the contract. Apart from laying down the common provision that should be included in the contract, this article also highlights the common mistakes that should be avoided even at the initial stage of the negotiation. This article concludes that ICT contract is becoming common, but the challenges are still there due to the rapid advancement of ICT.